A New Polythiophene Derivative for High Efficiency Polymer Solar Cells with PCE over 9%. Issue 14 (17th May 2016) - Fan, Qunping; Su, Wenyan; Guo, Xia; Guo, Bing; Li, Wanbin; Zhang, Youdi; Wang, Kun; Zhang, Maojie; Li, Yongfang
Abstract : A new fluorinated polythiophene (PT) derivative, PBDD‐ff4T, is designed and synthesized. The PBDD‐ff4T/PC71 BM‐based device without any extra treatment exhibits a high efficiency of 9.2%, under the irradiation of AM 1.5G, 100 mW cm −2, which is the highest power conversion efficiency reported for PT derivative‐based polymer solar cells.